THE INFLUENCE OF Cu CONCENTRATION ON Cu-ZEOLITE TO ANTIBACTERIAL POWER IN STREPTOCOCCUS MUTANS - Dyah Irnawati; Purwanto Agustiono; Endi Hanifah Wardhani (Jurnal Zeolit Indonesia, 2010)
Microorganisms on the mouth can cause disease on hard and soft muscular of the mouth. One of the microorganisms is a bacteria S. mutans which become etiology of dental caries. The copper (Cu) is one of chemical agents to control microorganism growth. The copper could be combined with zeolite as antibacterial materials. This study aimed to known the affect Cu concentration on Cu-Natural zeolite to antibacterial power of S. mutans. The study was conducted by making five groups of Cu-Zeolite are 0,05M, 0,1M, 0,15M, 0,2M, and 0,25M. 100 mesh zeolite powder was activated at temperature 200 oC during one hours. CuCl2 solution with concentration of 0,05 M until 0,25 M are made each with volume of 80 mL. Cu-zeolite made by reacting 2 gram of zeolite powder with 80 ml of CuCl2 solution for one hours at temperature of 100 oC, then filtered, washed, and dried on the oven at 100 oC during 24 hours. S. mutans bacterial (0,1 mL x 108 CFU/mL) were grown in solid media MHA, then Cu Zeolite (30 mg) was included on pitting at gel media an incubated for 24 hours at temperature 37 oC (n=5). Transulent zone diameter was measured with digital slide-term (0.01 mm). The data were analyzed by anava one stripe and HSH with level signification of 0,05. The result showed an average of translucent zones was 0 mm (0,05 M gropus), 16,03 + 0,47 mm (0,10M), 16,45 + 0,91 mm (0,15M), 18,08 + 0,39 mm (0,20M), and 18,26 + 0,68 mm (0,25M). Anava test showed Cu concentration on 0,10 M up to 0,25 M of Cu Natural zeolite was significantly effect on translucent zones of S. mutans (p< 0,01). The result of HSD showed a significantly difference among all gropus, except on 0,01 M and O,15 M, and 0,20 m and 0,25 m (p>0,05). Conclusion of this study is Cu concentration in Cu-natural zeolite has affected antibacterial power of S. mutans. 0,01 M of Cuconcentration in Cu-natural zeolite has an antibacterial power to S. mutans and highest antibacterial power was on concentration groups of 0,20M.